Aquatic biota of different karst habitats in epigean and subterranean systems of Central Brazil – visibility versus relevance of taxa - Luiza Simões; Tânia Ferreira; Maria Bichuette (Subterranean Biology, 2013)
The karstic area of São Domingos, central Brazil, holds extensive drainage systems. In order to understand its biodiversity, various volumes of water were filtered with planktonic nets in stretches of subterranean and superficial rivers on five different occasions. We sampled four drips (152L), three calcite pools (368L), two subterranean rivers fed mainly by percolation water (6,395L), two subterranean rivers fed mainly by water coming from a sinkhole (4,175L) along different caves, one resurgence (158L), and four epigean rivers (101,690L). Physical and chemical variables were measured at some sites. Canonical Correlation Analysis was used to verify relationships between taxa and environment. The degree of similarity of the biota was assessed by cluster analysis (Sorensen, single linkage). There were records of exclusive taxa in epigean and subterranean samples, mainly in drips, which harbour the most unique fauna. The high richness of taxa presently recorded reveals the potential of the vadose zone biota in the tropical region, which was neglected in studies on Brazilian subterranean biodiversity. According to our results, the unsaturated zone tropical fauna may have different composition compared to that from temperate habitats. The studied communities were dominated by rotifers, while crustacean are predominant in the latter. The hypothesis can be clarified with the increase of long term studies and taxa identification at species level, besides the use of complementary sampling methods.